Answer:
nfefn cjd cnd c
efnckjd sc
Step-by-step explanation:evs kd vjkdfxds
I agree with what that person told you. The expression -2(x+10) is equivalent to -2x-20
Multiply the outer -2 with the inner x to get -2 times x = -2x
Multiply the outer -2 with the inner term 10 to get -2 times 10 = -20
So overall, -2(x+10) = -2x-20
--------------------------------------------
So that's how we're able to go from this
![-2(x+10) \ge 75](https://tex.z-dn.net/?f=-2%28x%2B10%29%20%5Cge%2075)
to this
![-2x-20 \ge 75](https://tex.z-dn.net/?f=-2x-20%20%5Cge%2075)
The only thing that changes is the left side. The inequality sign will not flip. It only flips if we multiply both sides by a negative number.
Answer:
2.7
Step-by-step explanation: